Preparation, Characterization, and Property Evaluation of Liposomes Embedded with Xanthine Oxidase Inhibitory Peptide Derived from Penaeus monodon - Ni WANG; Qingze SUN; Hong JIANG; Jian'an SUN; Xiangzhao MAO (Shipin gongye ke-ji)
To address the issue of low stability in Xanthine oxidase inhibitory peptide from Penaeus monodon (XO-IPPM) during its application, this study aimed to explore the preparation of liposomes encapsulating XO-IPPM using an ethanol injection-assisted sonication technique. By utilizing encapsulation efficiency as a key performance indicator, the optimal conditions for liposome preparation were established through both univariate and orthogonal experimental approaches. The liposomes were characterized using various analytical techniques, including transmission electron microscopy (TEM), Fourier transform infrared spectrum (FTIR), thermogravimetric analysis (TG), and differential scanning calorimetry (DSC), and subjected to in vitro simulated digestion experiments. Results showed that, the optimal preparation conditions for liposomes were as follows: Concentration ratio of egg yolk lecithin to XO-IPPM of 5:4, mass ratio of whey protein powder to phospholipids of 1:3, volume ratio of organic phase to aqueous phase of 6:5, ultrasonication duration of 3 minutes, and ultrasonication power of 150 W. Under these optimized conditions, the liposomes exhibited an encapsulation efficiency of 90.53%±1.46%, with a particle size of 205.12±0.02 nm, a polydispersity index (PDI) of 0.160±0.291, and a zeta potential of −39.79±0.09 mV. TEM analysis revealed that the liposomes were spherical and homogeneously dispersed in solution. FTIR spectra indicated that the intermolecular interactions among the components facilitated effective encapsulation of XO-IPPM within the liposomes. Furthermore, TG and DSC demonstrated enhanced thermal stability of the liposome-encapsulated XO-IPPM compared to its free form. Notably, the xanthine oxidase inhibitory activity of liposome-encapsulated XO-IPPM (56.05%±1.08%) was significantly (P<0.05) superior to that of the free XO-IPPM (29.04%±1.42%). This research endeavors to elucidate the preparation process, characterization, and properties of liposomes embedded with XO-IPPM, aiming to safeguard the XO inhibitory activity of XO-IPPM and improve its stability throughout the application process.